23‐4: Full Color, Active‐Matrix Micro‐LED Display with Dual Gate a‐IGZO TFT Backplane. Issue 1 (25th September 2020) - Kim, Hyo-Min; Lee, Jiseob; park, Sungmin; Choi, Wonseok; Kim, Soohyun; Jeon, Ki-Seong; Choi, Yoon-Ho; Lee, Jeong-Soo; Jang, Jin
Abstract : A full color, active matrix micro‐LED (AMLED) display using dual‐gate (DG) a‐IGZO TFT and lateral micro‐LED chip is demonstrated. It is found that DG a‐IGZO TFT backplane is suitable for driving large area, full color micro‐LED display. In this research, the driving TFTs for red, green and blue µ‐LEDs exhibit a uniform threshold voltage (Vth ) and linear mobility characteristics as 0.4, 0.3 and 0.3 V, and 7.79, 7.83 and 7.78 cm 2 /Vs, respectively. Also, the full color AMLED display has a 58 ppi with diagonal 2‐inch and exhibits the wide color triangle as 110.5 % in National Television System Committee (NTSC) 1931.